Sustainable Performance: The Effects Of Sustainability, Strategic, Tactical Orientations And Csr Practices - Abulaziz H, Alhumaidan Abdullah (2020)
Sustainable performance is relatively a new topic in business’s field; however, the awareness of it is growing day by day. This attention on sustainability has made pressure against enterprises to attempt to satisfy its norms. In Tunisia, media and social media have raised their tune against organizations to perform sustainably since natural environment and local communities are affected by firms’ operations specifically, manufacturing sector. Although there are some studies have investigated such issues, many of them have focused on larger and multinational companies within western context with less attention on smaller enterprises. Thus, the thesis has made an attempt to examine sustainable performance in Tunisia across manufacturing SMEs. It aims to know the factors that could contribute positively on sustainable performance. Within this context, it has suggested some variables to respond to the research problem, and to overcome literature gaps. The study has proposed that SMEs owners’ orientations can affect sustainable performance since these types of organizations are widely affected by their managers’ personal factors. However, to gain deeper knowledge, it hypothesized that CSR practices might explain such relationships. These variables can be underpinned by stakeholder theory and UET due to these theories have focused on owners’ backgrounds and firms’ performance. Because of the research problem focuses on manufacturing sector, the thesis has adopted quantitative method with non-probability purposive sampling.